An Efficient Multiplex PCR-Based Assay as a Novel Tool for Accurate Inter-Serovar Discrimination of Salmonella Enteritidis, S. Pullorum/Gallinarum and S. Dublin - Xiong, Dan; Song, Li; Tao, Jing; Zheng, Huijuan; Zhou, Zihao; Geng, Shizhong; Pan, Zhiming; Jiao, Xinan (Frontiers in Microbiology, 2017)
Salmonella enterica serovars Enteritidis, Pullorum/Gallinarum, and Dublin are important infectious pathogens that have caused widespread problems for pig, chicken, and cattle production, respectively. Traditional Salmonella serotyping is costly and time-consuming. In this study, we developed a rapid multiplex PCR method to simultaneously distinguish the three prevalent Salmonella serovars Enteritidis, Pullorum/Gallinarum, and Dublin individually for the first time. The multiplex PCR-based assay focuses on three genes tcpS, lygD and flhB. Gene tcpS exists only in the three Salmonella serovars, and lygD exists only in S. Enteritidis, while flhB gene shows a deficient region only in S. Pullorum/Gallinarum, compared with that of other serovars. The specificity and sensitivity of the multiplex PCR assay using three pairs of specific primers for these genes were evaluated. The results showed that this multiplex PCR method could accurately identify Salmonella Enteritidis, Pullorum/Gallinarum, and Dublin from eight non-Salmonella species and 27 Salmonella serovars. The minimum concentration of DNA and the least number of cells that could be detected were 58.5 pg/μL and 100 CFU. Subsequently, the method was applied to analyze clinical Salmonella strains isolated from one pig farm, one chicken farm, and one cattle farm. The results showed that blinded PCR testing of Salmonella isolates from the three farms were in concordance with the traditional serotyping tests, indicating the newly developed multiplex PCR system could be used as a novel tool to accurately distinguish the three specific Salmonella serovars individually, which is useful, especially in high-throughput screening.